Acromegalic arthropathy of the hand with sesamoid involvement: a case report. - Kocakoc, Ercan; Kiris, Adem; Ozgocmen, Salih (My University, 2002)
Acromegalic arthropathy may affect the hand joints with characteristic radiological changes. Sesamoid involvement in the hand may be presented with unusual changes. A case of a female patient with characteristic hand joint and sesamoid bone osteophytic changes related to acromegalic arthropathy is presented.
Keywords: Acromegaly; Female; Humans; Joint Diseases; Middle Aged; Sesamoid Bones; acromegaly; arthropathy; article; case report; female; human; middle aged; radiography; sesamoid bone